Production of anti‐SARS‐CoV‐2 hyperimmune globulin from convalescent plasma. Issue 6 (22nd March 2021) - Vandeberg, Peter; Cruz, Maria; Diez, Jose Maria; Merritt, W. Keither; Santos, Benjamin; Trukawinski, Susan; Wellhouse, Andrea; Jose, Marta; Willis, Todd
Abstract: Background: In late 2019, the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) virus emerged in China and quickly spread into a worldwide pandemic. Prior to the development of specific drug therapies or a vaccine, more immediately available treatments were sought including convalescent plasma. A potential improvement from convalescent plasma could be the preparation of anti‐SARS‐CoV‐2 hyperimmune globulin (hIVIG). Study Design and Methods: Convalescent plasma was collected from an existing network of plasma donation centers. A caprylate/chromatography purification process was used to manufacture hIVIG. Initial batches of hIVIG were manufactured in a versatile, small‐scale facility designed and built to rapidly address emerging infectious diseases. Results: Processing convalescent plasma into hIVIG resulted in a highly purified immunoglobulin G (IgG) product with more concentrated neutralizing antibody activity. hIVIG will allow for the administration of greater antibody activity per unit of volume with decreased potential for several adverse events associated with plasma administration. IgG concentration and IgG specific to SARS‐CoV‐2 were increased over 10‐fold from convalescent plasma to the final product. Normalized enzyme‐linked immunosorbent assay activity (per mg/ml IgG) was maintained throughout the process. Protein content in these final product batches was 100% IgG, consisting of 98% monomer and dimer forms. Potentially hazardous proteins (IgM, IgA, and anti‐A, anti‐B, and anti‐D) were reduced to minimal levels. Conclusions: Multiple batches of anti‐SARS‐CoV‐2 hIVIG that met regulatory requirements were manufactured from human convalescent plasma. The first clinical study in which the hIVIG will be evaluated will be Inpatient Treatment with Anti‐Coronavirus Immunoglobulin (ITAC) [NCT04546581].